ASEAN as an international organization international law and region-building in Southeast Asia - Bagulaya, José Duke (University of Santo Tomas Publishing House, 2022)
The book critically examines ASEAN's transformation into an international legal entity, exploring the concept of "people" and offering a people's reading of the ASEAN Charter. It critiques ASEAN's constitutional, extra-constitutional, and practical limitations, while questioning the notion of community within ASEAN's discourses. Combining international law, politics, and culture, it offers insightful perspectives for legal scholars and students.